Construção e aplicação de um jogo de tabuleiro sobre a temática do consumo de energia elétrica residencial no contexto da sala de aula de física - Moura, Felipe Esteves (2020)
This research aims to stimulate the interest of the student in the teaching of Physics, through the ludic. For this purpose, a board game was built and applied on the theme of residential electricity consumption in the classroom context. The choice of theme is related to the student's difficulty in associating what is exposed in traditional class with their daily life, making the current teaching method discouraging. To do so, the work aimed to build and apply the board game to assist in the process of teaching and learning physics, guided by the theme of residential electricity consumption in the context of the classroom. In this way, a board game composed of questions and answers was elaborated and applied in a High School 3rd grade class. The methodology of this research is of a qualitative nature, of an exploratory character of the type case study. It was found that the interactive activity provided debates and discussions related to the theme of the game, causing the active participation of students and consequently an effective learning. The research also pointed out the board game as an alternative for teaching physics, as it brought theory and practice closer together, increasing the assimilation of knowledge through the interaction provided by the game.